2011
DOI: 10.1111/j.1464-410x.2011.10482.x
|View full text |Cite
|
Sign up to set email alerts
|

Stage‐specific impact of pelvic lymph node dissection on survival in patients with non‐metastatic bladder cancer treated with radical cystectomy

Abstract: 4 7What ' s known on the subject? and What does the study add? In patients treated with radical cystectomy, pelvic lymph node dissection may have a benefi cial effect on cancer control outcomes.We examined the effect of pelvic lymph node dissection on stage-specifi c cancer control outcomes. OBJECTIVE• To examine the effect of stage-specifi c pelvic lymph node dissection (PLND) on cancer-specifi c (CSM) and overall mortality (OM) rates at radical cystectomy (RC) for bladder cancer. METHODS• Overall, 11 183 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 11 publications
3
47
0
2
Order By: Relevance
“…In terms of overall survival at 18 months with a rate of 71.5% and no local recurrence, this series of patients with unifocal lateral wall MIBC are within the limits described in the literature, and 100% survival at 24 months for patients with T1 and T2 / N0 postoperative also [18]. Cancer specific deads were due to particular histological variants such as micropapillay variant which is asociated with aggresive behavior and poor prognosis [19] The limits of this study are given by the low number of patients enrolled, low follow-up period for survival and recurrence rate, but because we actually watched tumor stage and lymph node status before and after cystectomy this study fulfill the objectives and the good results reported to literature pleades for a standard PLND in these patients with a survival rate in patients with N0 according to previously published studies.…”
Section: Discussionsupporting
confidence: 72%
“…In terms of overall survival at 18 months with a rate of 71.5% and no local recurrence, this series of patients with unifocal lateral wall MIBC are within the limits described in the literature, and 100% survival at 24 months for patients with T1 and T2 / N0 postoperative also [18]. Cancer specific deads were due to particular histological variants such as micropapillay variant which is asociated with aggresive behavior and poor prognosis [19] The limits of this study are given by the low number of patients enrolled, low follow-up period for survival and recurrence rate, but because we actually watched tumor stage and lymph node status before and after cystectomy this study fulfill the objectives and the good results reported to literature pleades for a standard PLND in these patients with a survival rate in patients with N0 according to previously published studies.…”
Section: Discussionsupporting
confidence: 72%
“…In fact, the study aimed at evaluating the risk of omitting PLND and, according to guidelines recommendation, 1 the authors concluded suggesting that PLND should be carried out "whenever it can be safely performed". 4 In our series, at univariable analysis, the number of nodes removed (LN-c) was predictive of DFS (log-rank P = 0.003) and CSS (log-rank P = 0.018), but it failed to achieve statistical significance in multivariable analysis; this data would support the importance of defining the anatomical template of PLND, as the median LN-c was 29 and 18 in the e-PLND and s-PLND subgroups, respectively. The optimal LN-c cut-off point, based on which patients were divided into two subgroups, was 27 nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the therapeutic role of PLND, many authors showed the negative impact of omitting PLND on oncological outcomes; in a recent paper by Abdollah et al, 4 the authors carried out a retrospective analysis of data collected in the SEER database to address the stage-specific impact of PLND on survival of patients treated with RC. At multivariable Cox analysis, the risk of omitting PLND stratified for pT stage was significant in pTa/is (HR 2.09), in pT1 (HR 1.6), in pT2 (HR 1.68) and pT3 (HR 1.15), but not in pT4 (HR 1.11 [95% CI 0.96-1.28]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, there is a paucity of data comparing patients treated with radical cystectomy plus PLND vs. radical cystectomy alone, 4,5 and more specifically, data evaluating the potential therapeutic role of PLND according to patients age and comorbidity status are still lacking.…”
Section: Introductionmentioning
confidence: 98%